Etnografia della transizione culturale nelle comunità San del Kalahari - Zavattaro, Monica (2022)
During her palaeoanthropological and ethnoarchaeological research at the University of the Witwatersrand, South Africa, between 2007 and 2014, Lucinda Backwell privately collected a significant amount of objects produced by the San communities who currently live in Kalahari reserves, assigned to them by the governments of Botswana and Namibia: the villages around Tsumkwe, in the Nyae Nyae Conservancy, the village of Kacgae in the district of Ghanzi and the Transfrontier Park on the border between Botswana and South Africa. Initially motivated by the desire to offer some economic support to the communities by purchasing some products of their craftsmanship, the author realized that it would be important to document the culture of the San and the elements in transition. With this in mind, she put together a collection of over 400 artifacts, which in 2018 she donated to the Natural History Museum of Florence. This work aims to document the collection and highlight its ethnographic meaning, considering the archaeological traces that attest to the antiquity of the San culture, and the evidence on the current living conditions of a people threatened in their survival.